Ensiklopedia Digital Tumbuhan Tingkat Tinggi Dengan Fitur QR Code Sebagai Sumber Belajar Dunia Tumbuhan - Azis, Khalisha; Wiharto, Muhammad; Saenab, Sitti (Biology Teaching and Learning, 2018)
Abstract. This research aims to develop a digital encyclopedia of higher plants with barcode feature as a learning resource that are valid and practical. The process of developing learning resources of digital encyclopedia of higher plants is done by using ADDIE development model, i.e. analyze, design, development, implementation and evaluation. In this study was done by using technology, ie smartphones, using an application named Quick Response Code (QR Code) that can accommodate a full information of plants description in the form of text then encoding into a barcode. Based on the results of the study, the average value of each aspect, 4.7 to the validity that can be concluded that the development of digital encyclopedia learning resources included in the category of "very valid" (4.5 â‰¤ Va 5). As for practicality in terms of studentâ€™s responses had an average value 81.71%, showing a positive response category, as well as the responses of teachers has an average value of 87.41%, which indicates the category of a very positive response. Both of these indicate that the encyclopedia digital learning resources can be used as a source of practical learning and fun in learning activities outside the classroom. Keywords: learning resources, digital encyclopedia, QR code.